1991
DOI: 10.1152/jappl.1991.70.5.2242
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-diameter relationships of the upper airway in awake supine subjects

Abstract: In awake supine normal subjects, dimensional changes of the oropharyngeal airway were measured during exposure to negative intraluminal pressures. The pressure was generated 1) "actively" by subjects inspiring against an externally occluded airway or 2) "passively" by external suction at the mouth during voluntary glottic closure with no inspiratory effort. Airway dimensions were imaged with X-ray fluoroscopy and anteroposterior diameters measured at levels corresponding to cervical vertebra 3 and 4 (C3 and C4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Such measurements are of particular value in understanding the pathophysiology of OSA and in devising, applying, and determining the effectiveness of treatment modalities (1). In recent years, upper airway size and shape have been measured by a number of techniques, including CT (16)(17)(18), fluoroscopy (19,20), MRI (21)(22)(23)(24), nasoendoscopy (25)(26)(27)(28), and acoustic reflection (4,29,30). Although these studies have demonstrated important differences in pharyngeal shape and size between individuals with and without OSA, in terms of baseline anatomy (4,16,18,22,23,29,30) and dynamic behavior (17,(19)(20)(21)(24)(25)(26)(27)(28), the routine use of these technologies for study of the upper airway on repeated occasions and over prolonged periods in individuals is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Such measurements are of particular value in understanding the pathophysiology of OSA and in devising, applying, and determining the effectiveness of treatment modalities (1). In recent years, upper airway size and shape have been measured by a number of techniques, including CT (16)(17)(18), fluoroscopy (19,20), MRI (21)(22)(23)(24), nasoendoscopy (25)(26)(27)(28), and acoustic reflection (4,29,30). Although these studies have demonstrated important differences in pharyngeal shape and size between individuals with and without OSA, in terms of baseline anatomy (4,16,18,22,23,29,30) and dynamic behavior (17,(19)(20)(21)(24)(25)(26)(27)(28), the routine use of these technologies for study of the upper airway on repeated occasions and over prolonged periods in individuals is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to determine the factors that control airway patency, investigators have measured changes in airway size and shape to indirectly assess the mechanical properties of the pharyngeal wall, i.e. surrounding pharyngeal soft tissues (Wheatley et al 1991; Schwab et al 1995; Ryan & Love, 1996; Brennick et al 1998; Morrell et al 1998). While studies using conventional CT and MRI studies can determine the volume of pharyngeal wall soft tissue structures, these imaging techniques are unable to directly evaluate the mechanical properties of these soft tissues.…”
mentioning
confidence: 99%
“…It has been known for some time that the intraluminal pressure required to reopen an occluded pharynx is higher than that required to collapse the airway [1][2][3][4]. The hysteresis in the closing and reopening pressures suggests that surface tension may be important in maintaining airway occlusion during an apnoea.…”
mentioning
confidence: 99%